DOI: 10.11606/d.18.2019.tde-23052019-091011
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento em serviço de lajes mistas de aço e concreto ao longo do tempo

Abstract: MORAIS OLIVEIRA, L. A. In service behavior of steel-concrete composite slabs under the long-term conditions. 2019. 250p. Dissertation (M. Sc. in Civil Engineering (Structures))

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
0
0
1
Order By: Relevance
“…Nevertheless, the experimental investigations have shown that this procedure leads to non-conservative estimates of the deflections, such as for beams (Patel, Bhardwaj, Chaudhary & Nagpal, 2015), but especially for composite slabs subjected to higher loads (Costa et al, 2021). However, studies using more recent literature such as the Australian standard, which consider a different equation to calculate the effective moment of inertia and the influence of more variables on the deflection, have resulted in displacements closer to those observed experimentally, as demonstrated by Oliveira (2019).…”
Section: Introductionmentioning
confidence: 88%
“…Nevertheless, the experimental investigations have shown that this procedure leads to non-conservative estimates of the deflections, such as for beams (Patel, Bhardwaj, Chaudhary & Nagpal, 2015), but especially for composite slabs subjected to higher loads (Costa et al, 2021). However, studies using more recent literature such as the Australian standard, which consider a different equation to calculate the effective moment of inertia and the influence of more variables on the deflection, have resulted in displacements closer to those observed experimentally, as demonstrated by Oliveira (2019).…”
Section: Introductionmentioning
confidence: 88%
“…Essa fôrma foi estudada por Sieg (2015), que fez a análise teórica do perfil de aço e uma análise teórica e experimental de lajes mistas compostas por essa fôrma. Oliveira (2019) também empregou essa mesma fôrma de aço nas lajes mistas do seu trabalho, porém avaliando seu comportamento em serviço.…”
Section: Considerações Geraisunclassified